Angiotensin-Converting Enzyme Gene Insertion/Deletion Polymorphism and Small Vessel Cerebral Stroke in Indian Population - Puttachandra Prabhakar; Tanima De; Dindagur Nagaraja; Rita Christopher (International Journal of Vascular Medicine)
Background. Hypertension is an established risk factor for small-vessel cerebral stroke and the renin-angiotensin system plays an important role in the maintenance of blood pressure. We aimed at evaluating the contribution of the angiotensin-converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism to the risk of small-vessel stroke in south Indian population. Materials and Methods. We investigated 128 patients diagnosed with small-vessel stroke and 236 age, and gender-matched healthy controls. ACE I/D polymorphism was detected by polymerase chain reaction. Results. Hypertension was significantly more prevalent in the patient group and was associated with 6-fold increase in risk for stroke. ACE genotypes were in Hardy-Weinberg equilibrium in both patients and controls. Prevalence of DD, ID, and II genotypes in cases (34.4%, 43.7%, and 28%) did not differ significantly from controls (31.8%, 43.2%, and 25%). The polymorphism was not associated with small-vessel stroke (OR: 1.34; 95% CI: 0.52–1.55). However, diastolic blood pressure was associated with the ACE I/D genotypes in the patients. (DD; 90.2±14.2> ID; 86.2±11.9> II; 82.3±7.8 mm Hg,  P=0.047). Conclusion. Our study showed that hypertension, but not ACE I/D polymorphism, increased the risk of small-vessel stroke.